2020
DOI: 10.1038/s41467-020-14458-y
|View full text |Cite
|
Sign up to set email alerts
|

A specific prelimbic-nucleus accumbens pathway controls resilience versus vulnerability to food addiction

Abstract: Food addiction is linked to obesity and eating disorders and is characterized by a loss of behavioral control and compulsive food intake. Here, using a food addiction mouse model, we report that the lack of cannabinoid type-1 receptor in dorsal telencephalic glutamatergic neurons prevents the development of food addiction-like behavior, which is associated with enhanced synaptic excitatory transmission in the medial prefrontal cortex (mPFC) and in the nucleus accumbens (NAc). In contrast, chemogenetic inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(120 citation statements)
references
References 54 publications
6
114
0
Order By: Relevance
“…For these reasons, it is of vital importance to perform studies using different drugs belonging to different pharmacological families (not only opiates but also cannabinoids, such as THC, for which there are now interesting self-administration models (Spencer et al, 2018)). We also suggest that other addictions be examined, including food addiction (Domingo-Rodriguez et al, 2020; Mancino et al, 2015) or gambling (Winstanley and Clark, 2016) This shall improve our understanding of the differential mechanisms underlying the development of substance use disorders and addictions in general.…”
Section: Resultsmentioning
confidence: 99%
“…For these reasons, it is of vital importance to perform studies using different drugs belonging to different pharmacological families (not only opiates but also cannabinoids, such as THC, for which there are now interesting self-administration models (Spencer et al, 2018)). We also suggest that other addictions be examined, including food addiction (Domingo-Rodriguez et al, 2020; Mancino et al, 2015) or gambling (Winstanley and Clark, 2016) This shall improve our understanding of the differential mechanisms underlying the development of substance use disorders and addictions in general.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been reported that prelimbic to NAc pathway is involved in compulsive reward taking 31 . Afferents onto SPNs of the lDS, which is the major target of the projection from M1, also remained unchanged with our paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…mPFC to dorsomedial, OFC to central and M1 to dorsolateral striatum may all be implicated in compulsive reward seeking, but their respective role remains elusive. Contrasting mPFC hypofunction and OFC hyperfunction may both favour the appearance of compulsion 5,[29][30][31] . Motor cortex, believed to control habitual responding via its projection to the dorsolateral striatum, may be involved in compulsive drug seeking, if there is a failure to disengage habitual behaviour 32 .…”
Section: Introductionmentioning
confidence: 99%
“…order to alleviate the diminished reward, in which CB1 in dorsal telencephalic neurons occupies a key regulatory function. Supporting these findings, we have recently showed that the lack of CB1 in this neuronal subpopulation did not fully mitigate the development of food addiction but significantly promoted a resilient phenotype [33].…”
Section: Discussionmentioning
confidence: 68%
“…The progressive ratio (PR) schedule of reinforcement was used to evaluate the motivation for chocolate-flavored pellets. The response required to earn one single pellet escalated according to the following series: 1,5,12,21,33,51,75,90,120,155,180,225,260,300,350,410,465,540,630,730,850, 1000, 1200, 1500, 1800, 2100, 2400, 2700, 3000, 3400, 3800, 4200, 4600, 5000, and 5500. The maximal number of responses that the animal performed to obtain one pellet was the last event completed, referred to as the breaking point (BP).…”
Section: Glucose and Insulin Tolerance Testmentioning
confidence: 99%